PROTOCOL: Global elder abuse: A mega‐map of systematic reviews on prevalence, consequences, risk and protective factors and interventions. Issue 2 (27th April 2022) - Mikton, Christopher; Beaulieu, Marie; Yon, Yongjie; Cadieux Genesse, Julien; St‐Martin, Kevin; Byrne, Mark; Phelan, Amanda; Storey, Jennifer; Rogers, Michaela; Campbell, Fiona; Ali, Parveen; Burnes, David; et al.
Abstract: This is the protocol for a Campbell systematic review. The objectives are as follows: to produce a mega‐map which identifies, maps and provides a visual interactive display, based on systematic reviews on all the main aspects of elder abuse in both the community and in institutions, such as residential and long‐term care institutions.